2020
DOI: 10.1038/s41598-020-78737-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of newer technologies for the diagnosis of Mycobacterium tuberculosis infection in Brazilian people living with HIV

Abstract: Tuberculosis is the leading cause of death among people living with HIV (PLH). Preventive tuberculosis therapy reduces mortality in PLH, especially in those with a positive tuberculin skin test (TST). New, more specific technologies for detecting latent tuberculosis infection (LTBI) are now commercially available. We sought to analyse the cost-effectiveness of four different strategies for the diagnosis of LTBI in PLH in Brazil, from the Brazilian public health care system perspective. We developed a Markov st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…These skin tests have the advantages of the TST and IGRAs, which are characterized by simple operation, low cost, and easy reading of results, making it possible to apply them in countries with a high burden of TB and in poverty-stricken areas, especially in countries implementing universal BCG vaccination. Furthermore, increasingly emerging studies have demonstrated that these new skin tests show similar test positivity rates, safety profiles, and specificities to those of IGRAs and provide comparable results in terms of diagnosing patients with TB living with HIV and children infected with M. tuberculosis (Table 1; Litvinov et al, 2009;Aggerbeck et al, 2013;Hoff et al, 2016;Ruhwald et al, 2017;Aggerbeck et al, 2018;Steffen et al, 2020). Nevertheless, the potential drawbacks of these three new skin tests are worth noting.…”
Section: Novel Emerging Skin Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…These skin tests have the advantages of the TST and IGRAs, which are characterized by simple operation, low cost, and easy reading of results, making it possible to apply them in countries with a high burden of TB and in poverty-stricken areas, especially in countries implementing universal BCG vaccination. Furthermore, increasingly emerging studies have demonstrated that these new skin tests show similar test positivity rates, safety profiles, and specificities to those of IGRAs and provide comparable results in terms of diagnosing patients with TB living with HIV and children infected with M. tuberculosis (Table 1; Litvinov et al, 2009;Aggerbeck et al, 2013;Hoff et al, 2016;Ruhwald et al, 2017;Aggerbeck et al, 2018;Steffen et al, 2020). Nevertheless, the potential drawbacks of these three new skin tests are worth noting.…”
Section: Novel Emerging Skin Testsmentioning
confidence: 99%
“…In addition to the conventional TST, three novel strategies for the diagnosis of TB have been developed in recent years-Diaskintest (Generium Pharmaceutical, Moscow, Russia), C-Tb skin test (Statens Serum Institut, Copenhagen, Denmark), and EC-Test (Zhifei Longcom Biologic Pharmacy Co., Anhui, China) (Steffen et al, 2020;WHO, 2020). The Diaskintest is a new effective way to identify the initial presentation of TB and developed based on a fusion protein of the early secreted antigenic target 6 (ESAT-6) and culture filtrate protein 10 (CFP-10) antigens present in virulent strains of M. tuberculosis, which are absent in the BCG strain and in most NTMs.…”
Section: Novel Emerging Skin Testsmentioning
confidence: 99%
“…Base-case results from Kowada [13] showed that T-SPOT.TB dominated all other strategies whereas our results showed that T-SPOT.TB was dominated by QFT-GIT. Steffen et al [14] showed that new emerging tests (e.g. Diaskintest and QFT-Plus) were cost-saving against TST.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A scoping search of the literature identified five studies [13][14][15][16][17] that assessed the cost-effectiveness of diagnostic strategies for identifying LTBI in PWH. These studies provide useful clinical and economic evidence that may be used to support recommendations but there were several limitations noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation